Evaluation of the effect of virtual reality glasses on preoperativesurgical anxiety in adult patients - Güner, Semih; Ekinci, Osman; Baytar, Çağdaş; Mete, Burak (Scientific Reports in Medicine, 2025)
Objective: Patients often experience varying levels of anxiety before surgery. It is essential to assess and address preoperative anxiety for each patient to ensure optimal outcomes. This study aims to evaluate the effectiveness of virtual reality (VR) glasses in reducing preoperative anxiety in patients undergoing laparoscopic cholecystectomy. Method: This prospective, observational cohort study included 84 patients aged 18–65 scheduled for elective laparoscopic cholecystectomy with an American Society of Anesthesiologists (ASA) physical status of I or II. Participants viewed a 30-minute VR video using a smartphone and VR headset. Oxygen saturation and heart rate were recorded before and after the VR session. Additionally, patients completed the “Anxiety Specific to Surgery Questionnaire” both before and after the VR intervention. Results: The study included 84 patients undergoing laparoscopic cholecystectomy. The VR intervention significantly reduced preoperative anxiety, as indicated by the questionnaire results (p < 0.001), with a moderate effect size. Although heart rate decreased after the VR session, the change was not statistically significant. Conclusion: The use of VR significantly reduced preoperative anxiety in patients scheduled for laparoscopic cholecystectomy.